Level of Understanding of Paud Teachers About Stunting Mitigation in PAUD Units of Preschool Talaud Islands Regency North Sulawesi Province - Saune, Deice; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This study aims to determine the level of understanding of PAUD teachers about stunting mitigation in PAUD Units in Talaud Islands Regency, North Sulawesi Province. The researcher used a survey method by distributing questionnaires to PAUD teachers in Talaud Regency. With a sample of 35 teachers, the results showed that the level of understanding of PAUD teachers about stunting mitigation in PAUD Units in Talaud Islands Regency, North Sulawesi Province was